Workshop Pembuatan Gummy Candy Madu Kelulut Di Desa Bangun Rejo Kabupaten Kutai Kartanegara - Samsul, Erwin; Junaidin, Junaidin; Rijai, Laode; Ibrahim, Arsyik; Herman, Herman; Rusli, Rolan; Ahmad, Islamudin; Febrina, Lizma; Farah, Harra Ismi; Hikmawan, Baso Didik; Rija’i, Hifdzur Rashif; Supriatno, Supriatno; Rusman, Arman; Almeida, Maria; Riki, Riki; Arifuddin, M; Bone, Mahfuzun; Arifian, Hanggara; Setiawaty, Agus (Universitas Negeri Medan, 2025)
A workshop on making gummy candy based on stingless bee honey was held in Bangun Rejo Village, Kutai Kartanegara Regency, as an effort to empower the community through innovation in locally processed food products. The aim of this activity was to improve the skills of MSME actors and village residents in producing stingless honey gummy candy, and to elevate the added value of local honey. The methods used included a short theoretical session about the composition of stingless bee honey and the technical process of gummy candy production, a live demonstration, group practice among participants, as well as evaluation via pre-test and post-test on understanding and skills. The workshop was attended by 50 participants from various MSMEs and community groups. Results showed that after training there was an increase in participant understanding by approximately 75% compared to before the training. Furthermore, participants succeeded in making gummy candy with a chewy texture, the natural sweetness of stingless bee honey, and a distinctive aroma that was well accepted in organoleptic tests. This workshop made a tangible contribution to local product diversification, increasing production capacity, and the potential enhancement of village income through signature products based on stingless bee.